2015
DOI: 10.4162/nrp.2015.9.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect ofErythronium japonicumon the human breast cancer cell metastasis

Abstract: BACKGROUND/OBJECTIVESIn this study, the inhibitory effect of Erythronium japonicum extracts on the metastasis of MDA-MB-231 human breast cancer cell line was determined.MATERIALS/METHODSCells were cultured with DMSO or with 50, 75, 100 or 250 µg/ml of Erythronium japonicum methanol or ethanol extract.RESULTSBoth methanol and ethanol extracts significantly inhibited the growth and induced apoptosis of MDA-MB-231 cells in a dose-dependent manner. Erythronium japonicum extracts inhibited the adhesion of MDA-MB-23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…We performed an extract fractionation to identify the EJE component that most alleviated microglial activation and found it to be the butanol fraction, which suppressed LPS-induced microglial activation and largely increased HO-1 expression in BV2 cells. Erythronium japonicum consists of major components, including chlorogenic acid, caffeic acid, kaempferol, quercetin, astragalin, and isoquercitrin [4,46], which have preventive antioxidant and anti-inflammatory effects [16,[47][48][49][50]. Among these major components, the evidence has suggested that chlorogenic acid and caffeic acid could attenuate cognitive impairment and neurodegeneration-associated diseases [50].…”
Section: Discussionmentioning
confidence: 99%
“…We performed an extract fractionation to identify the EJE component that most alleviated microglial activation and found it to be the butanol fraction, which suppressed LPS-induced microglial activation and largely increased HO-1 expression in BV2 cells. Erythronium japonicum consists of major components, including chlorogenic acid, caffeic acid, kaempferol, quercetin, astragalin, and isoquercitrin [4,46], which have preventive antioxidant and anti-inflammatory effects [16,[47][48][49][50]. Among these major components, the evidence has suggested that chlorogenic acid and caffeic acid could attenuate cognitive impairment and neurodegeneration-associated diseases [50].…”
Section: Discussionmentioning
confidence: 99%